The life and times of Ethel Tawse Jollie : a case study of the transference and adaptation of British social and political ideas of the Edwardian era to a colonial society - Lowry, Daniel William (Rhodes University, Faculty of Humanities, Department of History, 1989)
This is an appraisal of the career of Ethel Tawse Jollie (1876-1950), the first woman parliamentarian in Southern Rhodesia, and the British Empire overseas, prolific writer and leading intellectual of her political generation who played a key role in the achievement of responsible government in Southern Rhodesia in 1923. As the founder and principal organiser of the Responsible Government Association she imported from Britain a singular political philosophy which made a lasting impression on Rhodesia's political character and social identity. She was an influential figure in British imperialist circles and in the women's suffrage controversy. No other Rhodesian politician had achieved such prominence in the metropole, or possessed such a thoroughly formed, comprehensive ideology, and the propaganda skills necessary to give it effect. The study traces the formation of her ideas within the intellectual milieu of pre-1914 Britain and - through her - its subsequent adaptation in Rhodesia; how, through her marriage to Archibald Colquhoun - explorer, writer and Cecil Rhodes's first Administrator of Mashonaland - she became steeped in the ideology of the Edwardian Radical Right - that reaction to imperial decline denoted by the slogan 'National Efficiency'. By 1915. when she arrived in Rhodesia, she had come to believe that by 1915, when she arrived in Rhodesia, she had come to believe that the salvation of the Empire lay in its 'patriotic' periphery where it was possible to create new societies on Radical Right principles. Both in and out of parliament she gave to Rhodesian public policy and identity a distinct Radical Right hue, which she further enhanced by her involvement in various extra parliamentary pressure groups. It is a life and times study and considerable use is made of contemporary ballads and novels in the belief that immersion in the atmosphere of the period is particularly useful in an intellectual biography of this kind. Comparisons are also made with other British peripheries notably Ulster, Canada and New Zealand. The study challenges the traditional view of Rhodesia as a neo-Victorian intellectual backwater; seeing it rather as a society which continued to import selectively ideas from elsewhere in the Empire. It should interest Commonwealth and - because of its central character - women's historians.
Keywords: Jollie, Ethel Tawse, 1876-1950; Zimbabwe -- History -- 1890-1965